Pendekatan Spiritual Islam sebagai Upaya Preventif Gangguan Mental Santri Era Society 5.0 di Madrasah Diniyyah Tanwirul Qulub Pamekasan - Roro Nofita Nofi; Imaniyatul Fithriyah (Pascasarjana IAI Al-Khairat Pamekasan, 2025)
This study aims to formulate a model of Islamic spiritual approach as a preventive effort against mental health disorders among students (santri) at Madrasah Diniyyah Tanwirul Qulub Pamekasan in the context of Society 5.0. The increasing psychological pressure faced by santri stemming from academic demands, adaptation to the pesantren environment, and uncontrolled use of digital technology serves as the key background of this research. Employing a qualitative-descriptive approach, data were collected through observation, in-depth interviews, and documentation, then analyzed thematically. Findings indicate several symptoms of mental disorders such as anxiety, insomnia, overthinking, and decreased learning motivation. However, various Islamic spiritual practices, including dhikr (remembrance of God), tazkiyatun nafs (soul purification), Sufi-oriented studies, and the active involvement of kiai and ustadz as spiritual mentors, have been proven effective in stabilizing the emotional condition of the students. Based on these findings, the study proposes a Preventive Islamic Spiritual Approach Model consisting of five core components: integration of worship and spiritual counseling, habitual dhikr and soul purification, Islamic digital mindfulness, the role of psycho-spiritual mentors, and a spiritually supportive environment. This model is contextually relevant, adaptive to the challenges of Society 5.0, and potentially replicable in other Islamic boarding schools. The study contributes conceptually to strengthening mental health based on Islamic values and opens new perspectives for transformative Islamic education in addressing the psychosocial challenges of the younger generation.